MAPPING THE POETIC METAPHORS IN THE ABSTRACT VISUAL ARTS - Kalla, Amit; Thakuriya, Kajal (International Journal of Research -GRANTHAALAYAH, 2025)
This swift study examines poetic metaphors in the visual arts, emphasizing the dynamic relationship between abstraction and context. To convey their abstract sentiments, artists employ a variety of techniques, fusing visual suggestion and symbolism to bridge the gap between the material and the immaterial. Interpreting these analogies requires consideration of cultural, historical, and individual factors. In the end, this study highlights how context and reference aid in revealing the hidden levels of meaning in abstract visual compositions.